The Conceptualization of Verb Meanings in the Kedah Subdialect (Jurnal Bahasa, 2024)
The formation of dialects is influenced by the geographical boundaries within which speakers reside. Such boundaries give rise to a variety of local dialects, including the Kedah, Pahang, Kelantan, and Terengganu dialects, as well as distinct subdialects within each region. Existing studies on the Kedah dialect are often focused on linguistic and sociolinguistic dimensions. Accordingly, this paper seeks to identify and conceptualize the meanings of selected verbs namely “bercerau”, “berceretet”, “berkenjah” and “berjabu” in the Kedah dialect, covering Northern, Central, and Southern Kedah. This qualitative research utilizes structured and unstructured interviews alongside a lexical register approach, as outlined by Asmah Haji Omar (2001), to explore and interpret the conceptualize of specific verbs in the Kedah Malay Dialect (KMD) as used by native speakers. Findings indicate that verbs in the Kedah dialect (across Northern, Central, and Southern regions) are conceptualized with nuanced meanings, reflecting the speakers' experiences and their geographical regions. Additionally, the study highlights instances where verb meanings are shared across regions and instances where they are unique to specific areas. This study aims to contribute to the preservation and documentation of the Kedah dialect, underscoring its distinctive linguistic heritage.Keywords: Dialect, Kedah Malay dialect, Kedah subdialect, verbs, Malay linguistics, meaning conceptualizationFull text: PDF